1997
DOI: 10.1183/09031936.97.10112560
|View full text |Cite
|
Sign up to set email alerts
|

Breathing pattern during acute respiratory failure and recovery

Abstract: The objective of this study was to compare the breathing pattern of patients who failed to wean from mechanical ventilation to the pattern during acute respiratory failure. We hypothesized that a similar breathing pattern occurs under both conditions. Breathing pattern, mouth occlusion pressure (P0.1) and maximum inspiratory pressure (PI,max) were measured in 15 patients during acute respiratory failure, within 24 h of the institution of mechanical ventilation, and in 49 patients during recovery, when they wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
1

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 33 publications
1
24
1
Order By: Relevance
“…The ventilatory pattern of www.intechopen.com patients that are not successfully weaned is similar to that observed during AFR (Del Rosario et al, 1997). Thus, some investigators recommend inspiratory muscle strengthening to reduce respiratory muscle fatigue (Chang, Boots, Brown, et al, 2005) and facilitate weaning from MV (Del Rosario et al, 1997).…”
Section: Weaning and Extubationmentioning
confidence: 77%
See 1 more Smart Citation
“…The ventilatory pattern of www.intechopen.com patients that are not successfully weaned is similar to that observed during AFR (Del Rosario et al, 1997). Thus, some investigators recommend inspiratory muscle strengthening to reduce respiratory muscle fatigue (Chang, Boots, Brown, et al, 2005) and facilitate weaning from MV (Del Rosario et al, 1997).…”
Section: Weaning and Extubationmentioning
confidence: 77%
“…J. Martin, et al, 2005). Although some studies recommend IMT during MV (Chang, Boots, Brown, et al, 2005;Del Rosario, et al, 1997;Sprague & Hopkins, 2003), observed a post-weaning reduction in inspiratory muscle strength in patients submitted to long-term MV.…”
Section: Effects Of Inspiratory Muscle Training On the Weaning Procesmentioning
confidence: 99%
“…In a previous study, patients with acute respiratory failure had a mean RSBI of 140 Ϯ 25 (breaths/min)/L. 2 From that datum we calculated that 14 patients were sufficient to detect RSBI changes of Ͼ 20% with a power of 80% and a significance level of .05. We first compared the 3 conditions without remifentanil (ie, before infusion of placebo, after infusion of placebo, and before infusion of remifentanil) with repeated-measure analysis of variance or the Friedman test, as appropriate.…”
Section: Discussionmentioning
confidence: 98%
“…[1][2][3] The rapid shallow breathing index (RSBI, respiratory rate divided by V T ) predicts weaning outcome, 4 extubation failure, 5 and time to wean. 6 Rapid shallow breathing is associated with increased ventilatory work load and/or reduction in respiratory muscle strength, and therefore can lead to respiratory muscle fatigue.…”
Section: Introductionmentioning
confidence: 99%
“…Both patients had HRF with inspiratory mouth pressures comparable to patients with acute HRF and those with weaning failure indicating an increased inspiratory load and decreased inspiratory muscle strength even after adequate treatment of pneumonia, sepsis and associated complications [13, 14, 15]. Decreased pulmonary compliance and increased alveolar dead space following fibrosing alveolitis might have contributed to HRF, but this was probably not the only condition which resulted in impairment of the respiratory pump, since fibrosing alveolitis due to ARDS, in general, leads to persistent hypoxemia, but not to hypercapnia [9].…”
Section: Discussionmentioning
confidence: 99%